BRAIN NATRIURETIC PROPEPTIDE AS A MARKER OF THE HEART DAMAGE IN METABOLIC SYNDROME - R. A. Libis; E. N. Isaeva; L. G. Vdovenko; I. R. Basyrova (Российский кардиологический журнал, 2015)
Aim. To study the relationship of NT-proBNP level with metabolic sindrome (MS) components and values of diastolic and systolic functions of the LV in patients with MS. Material and methods. Totally 148 patients studied. The main group consisted of 100 persons with MS, controls were 48 persons without MS. The participants underwent anthropometry, BP measurement, glucose level measurement, lipid spectrum, NT-proBNP levels and also ECG and EchoCG recording. MS and its components were evaluated according to IDF (2005).Results. MS patients had higher level of NT-proBNP than controls (246,5±35,3 pg/ml vs 24,33±4,7 pg/ml, p<0,0001). It was shown that the diameter of LA (P=0,766, p=0,001), IVST (P=0,29, p=0,04), ОТ (Р=-0,217, p=0,039) and level of TG (P=-0,22, p=0,04) are independent factors related to NT-proBNP. With anincrease of diastolic dysfunction LV severity the level of NT-proBNP alsoincreased.Conclusion. NT-proBNP reveals the patients with early cardial disorders amongpersons with MS.